2015
DOI: 10.1155/2015/583851
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Metastasis from Penile Carcinoma: Report of 2 Cases

Abstract: Purpose. Penile cancer rarely gives symptomatic skeletal metastases. Methods. We present 2 patients with squamous carcinoma of the penis who were surgically treated for metastases in the femur. Results. Both patients had pathological fractures and were operated on. In one case, the skeletal metastasis preceded any lymphatic spread of the disease, suggesting early haematogenous dissemination. Conclusions. Endoprosthetic reconstruction resulted in pain relief and restored the ambulatory capacity. Clinicians shou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 6 publications
0
14
0
Order By: Relevance
“…MRI supports the investigation of local staging (Kayes et al 2007 ). Bone metastases are uncommon and are usually associated with more advanced disease; therefore, patients should not routinely undergo bone scans unless they present signs and symptoms such as pain or increased alkaline phosphatase elevation (recommendation, LE: 4) (Braumann et al 2015 ; Lal et al 1999 ; Jacob et al 1995 ). …”
Section: Resultsmentioning
confidence: 99%
“…MRI supports the investigation of local staging (Kayes et al 2007 ). Bone metastases are uncommon and are usually associated with more advanced disease; therefore, patients should not routinely undergo bone scans unless they present signs and symptoms such as pain or increased alkaline phosphatase elevation (recommendation, LE: 4) (Braumann et al 2015 ; Lal et al 1999 ; Jacob et al 1995 ). …”
Section: Resultsmentioning
confidence: 99%
“…13,14 The review of literature of anecdotal reports suggests metastasis of penile cancer to lungs, liver, brain, skeleton, heart, retroperitoneum, skin of neck, and breast. 6,13,[15][16][17][18][19] In the first reported case of breast metastasis, the patient presented with a 2-cm irregular shaped lump, palpable near his left nipple. 6 The patient reported here, presented to us with an erythematous hard periareolar swelling lying in outer quadrant of right breast.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of bony metastatic lesion needs to be individualized. Since the patient was young, with favorable histology of the primary tumor with absence of visceral metastasis and a good progression-free survival of 1.5 years, the option of resecting the metastatic bony lesion with curative extent along with prosthetic reconstruction could have been reasonable in the case [3]. However, such an option entails higher cost and needs more expertise which may not always be available in our country.…”
Section: Respected Sirmentioning
confidence: 99%
“…Mirels developed a scoring system to diagnose bones at risk of impending fracture which can be applied in cases similar to this. Also, the author should have done proper literature search before labeling the case as Bthe first case being reported.^A simple Google search revealed that two similar cases have been reported in 2015 by Braumann et al [3]. Also, the image given in the text shows that the chest X-ray has been uploaded in the wrong orientation (the heart apex points toward the right).…”
Section: Respected Sirmentioning
confidence: 99%